Smartphone Ecosystem Switching from Android to iOS: A Push Pull Mooring Perspective - Rifqi Rafi, Muhammad; Elvira Azis (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines smartphone ecosystem switching from Android to iOS using the Push-Pull-Mooring framework. It investigates the effects of push, pull, and mooring factors on switching intention and the effect of switching intention on switching behaviour among Indonesian university students. Using a quantitative survey and PLS-SEM analysis with SmartPLS 4, the results show acceptable outer loadings and moderate explanatory power. Push, pull, and mooring factors explain 58.5% of switching intention, while switching intention explains 52.1% of switching behaviour. The findings imply that ecosystem migration is shaped by dissatisfaction, alternative attraction, and switching constraints.